Recent Developments in Piezoresistive Pressure Sensors: Materials, Architectures, and Applications (2018–2024) (International Journal of Scientific Research in Science and Technology, 2025)
Piezoresistive pressure sensors (PPS) remain the workhorse of pressure sensing across industries owing to their simple readout, CMOS-compatibility, and wide dynamic range. Over the past five years, PPS research has accelerated along three vectors: (i) materials innovation spanning silicon-on-insulator (SOI), wide–band-gap semiconductors (SiC), 2D materials (graphene, MoS₂), MXenes, metal–organic frameworks (MOFs), and conductive polymer nanocomposites; (ii) micro/nano-architectures that amplify gauge factor via crack engineering, hierarchical porosity, and microdome/pyramidal elastomeric structures; and (iii) application-driven designs for flexible/wearable e-skins, harsh environments (≥300 °C), and miniature biomedical catheters/microfluidics. This review synthesizes developments from roughly 2018–2024, covering device physics, fabrication, performance benchmarks (sensitivity, limit of detection, drift, hysteresis, bandwidth), temperature compensation, reliability, and system-level integration. We conclude with open challenges—standardized benchmarking, long-term stability, temperature/creep mitigation, and sustainable manufacturing—and outline promising research directions including printable PPS, multi-modal fusion, AI-assisted calibration, and biodegradable/implantable platforms.